Advantages of colour flow imaging in the diagnosis of left ventricular pseudoaneurysm. Issue 1 (January 1989) - Sutherland, G R; Smyllie, J H; Roelandt, J R
Abstract : Eleven cases of left ventricular pseudoaneurysm in nine patients were studied by cross sectional echocardiography, conventional Doppler echocardiography, and colour flow imaging. In two patients recurrent pseudoaneurysms developed after cardiac surgery, three had acute rupture after myocardial infarction, two were the result of stab wounds, one was a late rupture of a true left ventricular aneurysm, one developed after surgical resection of a true left ventricular aneurysm, and two as a consequence of left ventricular venting. In all 11 cases the diagnosis was confirmed by angiographic or surgical information or both. The diagnosis was suspected clinically in only four cases. Cross sectional echocardiography alone confirmed the diagnosis in five cases. Neither pulsed wave Doppler nor continuous wave Doppler established the diagnosis when they were used without colour flow imaging in five and three cases respectively. In all 11 cases colour flow imaging showed flow in and out of the pericardial cavity at the defect site as well as the abnormal flow within the pseudoaneurysm. Subsequent use of pulsed Doppler showed a consistent "to and fro" flow pattern across the myocardial defect with characteristic respiratory variation of the peak systolic velocity. This unique intrapericardial flow pattern is diagnostic of a pseudoaneurysm. Colour flow imaging is a valuable addition to cross sectional and Doppler echocardiography, and is the best technique for detecting left ventricular pseudoaneurysms.